Metabolismo de proteínas na musculatura esquelética de ratos submetidos à dieta hipoproteica-hiperglicídica durante a fase de crescimento - Batistela, Emanuele (2012)
The objective of this study was to evaluate the changes in protein metabolism in soleus muscles of growing rats submitted to low-protein, high-carbohydrate (LPHC) diet, in order to clarify the differential contribution of components of protein degradation pathways and of factors involved in their regulation. Male Wistar rats with 30 days old were fed a LPHC (6% protein; 74% carbohydrate) or control diet (C, 17% protein; 63% carbohydrate) for 15 days. At the end of this period, the animals were euthanized to collect soleus muscles, which were used for analysis. The rate of protein synthesis was determined by incorporation of L-[U14C] tyrosine and of overall proteolysis by the measurement of tyrosine released into the incubation medium by fluorimetric method. The protease activities were assessed by the hydrolysis of specific substrates for each enzyme, with release of aminomethylcoumarin (AMC), quantified by fluorimetric method. It was evaluated the gene expression of atrogenes and calpastatin by quantitative PCR. Protein levels of components that belong to proteolytic processes or to insulin and AMPK cascades were investigated through Western blotting. Results were expressed as mean ± SEM and evaluated by Student's t test or two-way ANOVA (P<0.05). It was not observed changes in the rate of protein synthesis, but the rate of overall proteolysis was lower in soleus from LPHC animals. Corroborating this finding, it was observed a decrease in the ubiquitin conjugates content and in the chymotrypsin-like activity of the proteasome, despite the atrogin-1 mRNA levels did not differ between groups. There was a decrease in caspase-3 protein levels and activity in soleus from LPHC animals. The calpain protein levels and activity showed an increase, while calpastatin mRNA levels were lower in soleus from LPHC animals. The cathepsin B protein levels were higher in soleus from LPHC animals, although the protease activity has presented no difference between the groups. The gene transcription and protein levels of LC3 were lower, as well as the protein levels of GABARAP, despite the increase in the gene transcription of this autophagic component in soleus from LPHC animals. There was an increase in the protein levels of insulin receptor and in the insulin-stimulated phosphorylation of AKT in soleus from LPHC animals, as well as in the protein content and phosphorylation of AMPK. The decrease in the overall protein degradation in soleus muscles from animals adapted to LPHC diet was associated to the inhibition in the caspase-3 activity and in the ubiquitin-proteasome system participation. The increased insulin sensitivity in soleus muscle seems to be involved in the inhibition of these proteolytic processes, probably due to the activation of AMPK in this tissue.